Study on the denitrification and dephosphorization of the aqueous solution by Chitosan/4A Zeolite/Zr based Zeolite. Issue 2 (15th January 2021) - Zhang, Yuanling; Yang, Min; Gui, Hua; Zhao, Tiantian; Tan, Wei; Wang, Hongbin
ABSTRACT: The ternary hybrid material chitosan/4A Zeolite/Zr based Zeolite was synthesized by using 4A zeolite molecular sieve, Zr-zeolite and chitosan acetic acid solution as starting materials. The prepared composite were characterized by SEM, FT-IR and XRD. The experimental conditions such as the concentration of chitosan acetic acid solution, mass ratio of mass ratio of chitosan acetic acid solution, 4A zeolite molecular sieve and Zr-zeolite functional material, the optimum calcination temperature were optimized. Under this optimum conditions, the denitrification and dephosphorization effect can reach more than 70% when pH value was at 3–9. Dynamics research results showed that the ammonia nitrogen and phosphorus removal progress by chitosan/4A Zeolite/Zr based Zeolite was in accordance could be well described by the pseudo-second-order kinetic model, and the adsorption rate is up to 6.439 g/min. The isothermal adsorption process was in accordance with Freundlich model. GRAPHICAL ABSTRACT: UF0001